On-demand fully customizable drug tablets via 3D printing technology for personalized medicine - Tan, Yan Jie Neriah; Yong, Wai Pong; Kochhar, Jaspreet Singh; Khanolkar, Jayant; Yao, Xiukai; Sun, Yajuan; Ao, Chi Kit; Soh, Siowling (Journal of controlled release, 2020)
Personalized medicine should ideally be prescribed to every individual because of the unique characteristics (e.g., biological, physical, and medical) of each individual. It is, however, challenging to provide personalized medicine for the mass population of specific individuals effectively and efficiently. This manuscript describes a method of fabricating fully customizable drug tablets for personalized medicine by the 3D printing technology. This method involves the versatile fabrication of the tablets via the specifically designed 3D printed molds of different shapes and sizes, and an intuitive 1-dimensional release of drug that relates the shape of the drug-containing matrix to the release profile. The customization includes all the aspects of varying dosage, duration, release profiles, and combination of multiple drugs. In particular, it has previously been technically difficult to devise a single platform that fabricates carriers that release drug with any desired type of release profiles. This method of fabricating fully customizable tablets is simple, inexpensive, and efficient. Detailed selection and investigation of the materials ensured that the tablet and the method of fabrication are safe (e.g., biocompatible, FDA-approved ingredients used) and other desirable features (e.g., sustained release and high dosage) are achieved. These desirable characteristics of the method thus allow fully customizable drug tablets to be fabricated efficiently on the spot after the diagnosis of individual patients; at the same time, the method can be made widely accessible to the mass population. Hence, the concept of personalized medicine can truly be realized. [Display omitted] •Fully customizable drug tablets were prepared via the 3D printing technology for personalized medicine.•Customization includes all aspects of dosage, duration, release profiles, and combination of multiple drugs in a single tablet.•Wide range of customization demonstrated, including high drug loading and sustained release.•Method is simple, inexpensive, safe, and versatile.•Individually customized drug tablet can thus be made widely accessible for realizing the concept of personalized medicine.